Financial Management for Improving Quality: A Case Study of SD Negeri 1 Candisari, Temanggung Regency - Cahyani, Wiwin; Nurkolis, Nurkolis; Wuryandini, Endang (Lembaga Teewan Journal Solutions, 2026)
This study aimed to analyze the implementation of financial management in improving educational quality at SD Negeri 1 Candisari, Bansari District, Temanggung Regency, focusing on three main functions: budgeting, accounting, and auditing. A qualitative approach with a phenomenological design was employed to obtain an in-depth understanding of school financial management practices. Data were collected through in-depth interviews with the principal, treasurer, teachers, and school committee members, supported by observations and document analysis. Data validity was ensured through source and technique triangulation, while data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings reveal that financial management has been systematically implemented through participatory budgeting based on the School Activity and Budget Plan (RKAS), Education Report Cards, and Data-Based Planning. The accounting function was conducted through transparent and accountable financial recording using official bookkeeping documents and digital reporting systems. Meanwhile, the auditing function involved internal and external supervision, periodic financial reporting, and continuous evaluation to ensure regulatory compliance and effective resource utilization. These integrated financial management practices contributed to improving school governance, strengthening accountability, supporting evidence-based decision-making, and enhancing educational quality. The study highlights that effective financial management is determined not only by funding availability but also by the quality of planning, financial administration, and supervision.